Ekuitas Merek, Gaya Hidup, dan Pembelian Bobabox: Studi pada Generasi Z - Denissa Aldana; Syafrida Hafni Sahir (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this research is to explore the relationship between brand equity, lifestyle, to the purchase decisions of generation Z consumers on Bobabox drinks in Medan Sunggal District. The research employs an associative quantitative method with data collected through observation and questionnaires. The population consisted 45.083 people, with 100 respondents from generation Z in Medan Sunggal District as the research sample. The sample was taken using the slovin formula and the questionnaire was distributed through a purposive sampling approach with the distribution of questionnaires using non-probability sampling to generation Z in Medan Sunggal District, Tanjung Rejo (Bobabox Setia Budi) and Sei Sikambing B (Bobabox Kasuari). Hypothesis testing of multiple linear regression analysis and descriptive analysis are methods of analyzing data. Based on the research results, it shows that: (1) Brand Equity (0,000 < 0,05) and tcount > ttable 3,910 > 1,984) have a positive and significant influence on the Purchase Decision of Bobabox drinks ; (2) The Purchase Decision of Bobabox drinks affects Lifestyle (0,000 < 0,05) and tcount > ttable (6,203 > 1,984) significantly and positively ; (3) The Purchase Decision of Bobabox drinks is positively, significantly and simultaneously influenced by the Brand Equity and Lifestyle factors (0,000 < 0,05) Fcount > Ftable (107,183 > 3,09). The Lifestyle and Brand Equity variables have an influence of 68,2% on the Purchase Decision from the determination coefficient, the remaining 31,8% is influenced by other factors not included in this research.